Patient considerations in the management of menopausal symptoms: role of conjugated estrogens with bazedoxifene - Kagan R; Goldstein SR; Pickar JH; Komm BS (Dove Medical Press, 2016)
Risa Kagan,1,2 Steven R Goldstein,3 James H Pickar,4 Barry S Komm5 1Department of Obstetrics, Gynecology and Reproductive Sciences, University of California, San Francisco, 2East Bay Physicians Medical Group, Berkeley, CA, 3Department of Obstetrics and Gynecology, New York University School of Medicine, 4Department of Obstetrics and Gynecology, Columbia University Medical Center, New York, NY, 5Global Medical Affairs, Pfizer Inc., Collegeville, PA, USA Abstract: Menopausal symptoms (eg, hot flushes and vaginal symptoms) are common, often bothersome, and can adversely impact women’s sexual functioning, relationships, and quality of life. Estrogen–progestin therapy was previously considered the standard care for hormone therapy (HT) for managing these symptoms in nonhysterectomized women, but has a number of safety and tolerability concerns (eg, breast cancer, stroke, pulmonary embolism, breast pain/tenderness, and vaginal bleeding) and its use has declined dramatically in the past decade since the release of the Women’s Health Initiative trial results. Conjugated estrogens paired with bazedoxifene (CE/BZA) represent a newer progestin-free alternative to traditional HT for nonhysterectomized women. CE/BZA has demonstrated efficacy in reducing the frequency and severity of vasomotor symptoms and preventing loss of bone mineral density in postmenopausal women. CE/BZA provides an acceptable level of protection against endometrial hyperplasia and does not increase mammographic breast density. Compared with traditional estrogen–progestin therapy, it is associated with lower rates of breast pain/tenderness and vaginal bleeding. Patient-reported outcomes indicate that CE/BZA improves menopause-specific quality of life, sleep, some measures of sexual function (especially ease of lubrication), and treatment satisfaction. This review looks at the rationale for selection and combination of CE with BZA at the dose ratio in the approved product and provides a detailed look at the efficacy, safety, tolerability, and patient-reported outcomes from the five Phase III trials. Patient considerations in the choice between CE/BZA and traditional HT (eg, tolerability, individual symptoms, and preferences for route of administration) are also considered. Keywords: menopause, conjugated estrogens/bazedoxifene, hormone therapy, hot flashes, osteoporosis, safety